The Prevalence of Anabolic-Androgenic Steroids Abuse, Knowledge and Attitude of Their Side Effects, and Attitude Toward Them Among the Female Bodybuilding Athletes in Kermanshah - Mehry Hoseini; Behram Yousefi; Ali Ashraf Khazaei (Fasa University of Medical Sciences, 2020)
Background & Objective: Anabolic-androgenic steroid abuse is one of the major problems in many kinds of sports, especially bodybuilding. The present study aimed at investigating the prevalence of anabolic-androgenic steroids abuse, knowledge and attitude of their side effects, and attitude toward them among the female bodybuilding athletes in Kermanshah. Materials & Methods: The present study is a descriptive one. The target population included all female bodybuilding athletes in Kermanshah. The measuring instruments were self-reported AAS questionnaires, including 25 questions (7 questions on background information, nine questions related to knowledge, and four questions related to attitudes, and five questions related to the prevalence of abuse) (Cronbach Alpha 0.84) which were distributed among 150 female bodybuilding athletes in Kermanshah. The collected data were analyzed by descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (Pearson correlation coefficient test, t-test) was used for data analysis. Results: The results of data analyses indicate that anabolic androgenic Steroids are used currently by 36.66% of the athletes. The main reason for using these drugs is the increase in muscular tissues and strength. There was a significant negative relationship between the prevalence of anabolic-androgenic steroids consumption and attitude, awareness, and educational level. Also, there was a significant relationship between sports history with the prevalence of anabolic-androgenic steroids consumption, attitude, and awareness. Conclusion: The female bodybuilder awareness of drug complications was significantly low. Increasing the rate of AAS consumption seems to become a public health concern that implies the need to implement educational programs by health care professionals and sports specialists.